Associations between Traditional Chinese Medicine Five-Emotion Responses and Menstrual Distress Symptoms across Menstrual Cycle Phases in Japanese Women - Xiaoyu Wu (Journal of Alternative, Complementary & Integrative Medicine, 2026)
TCM Five-Emotion responses were significantly associated with menstrual distress symptoms among Japanese women